The Pedagogy of Intimacy: Mother's Contribution to Academic Parenting during Student's Learning from Home - Mutiara Andalas (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
This essay strives to articulate the pedagogy of intimacy born from mothers' engagement in academic parenting when formal learning shifts from school to home. Redefining parenting and intimacy, mothers implicitly articulated an alternative pedagogy when the space and time of learning during the Covid-19 pandemic move to home. Listening to the self-narratives of mothers who work full time at home, at least part-time, as informants in thisqualitative study, the words